Viscoelastic Properties of ECM-Rich Embryonic Microenvironments - Akos, Zsuzsa; Isai, Dona Greta; Rajasingh, Sheeja; Kosa, Edina; Ghazvini, Saba; Dhar, Prajnaparamita; Czirok, Andras (Frontiers in Cell and Developmental Biology, 2020)
The material properties of tissues and their mechanical state is an important factor during development, disease, regenerative medicine and tissue engineering. Here we describe a microrheological measurement technique utilizing aggregates of microinjected ferromagnetic nickel particles to probe the viscoelastic properties of embryonic tissues. Quail embryos were cultured in a plastic incubator chamber located at the center of two pairs of crossed electromagnets. We found a pronounced viscoelastic behavior within the ECM-rich region separating the mesoderm and endoderm in Hamburger Hamilton stage 10 quail embryos, consistent with a Zener (standard generalized solid) model. The viscoelastic response is about 45% of the total response, with a characteristic relaxation time of 1.3 sec.